The Building of Country Manager's Competence and Its Use to Orchestra Subsidiary's Resources: Empirical Study of Indonesian Subsidiaries in Nigeria - So Yohanes Jimmy; Firmanzah Firmanzah; Tengku Ezni Balqiah; Albert Widjaja (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
This study employs resource orchestration model to investigate the influence of country manager’s competence on subsidiary performance in host country. Structural equation model with multisteps approach is operated using Lisrel to analyze 41 data from Indonesian business unit operating in Nigeria. This study found that country managers uses subsidiary absorptive capacity, which is formed by the combination of headquarter and local partner resources, as the dominant source of learning to develop their competence overtime. This competence does not directly influence subsidiary performance, but it is notably used to accumulate the critical assets for their subordinate business units. These assets then become valuable inputs for business units to develop or modify their operational capabilities, which directly influence the performance. One contribution of this study is providing more detail explanation of how headquarter resources invested abroad are transformed into subsidiary performance.